Cultures in conflict social movements and the state in Peru - Stokes, Susan C. (Univ. of California Press, 1995)
"Ethnography by a political scientist focuses on how urban poor have changed their perceptions of the State, citizenship, class and gender relations, and democracy and have movilized radical social movements. Analysis includes historical and ethnographic components"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/